Silane-Modified Graphene Oxide Composite as a Promising Corrosion-Inhibiting Film for Magnesium Alloy AZ31 - Zhang, You; Wang, Juping; Zhang, Zheng; Wei, Kai; Zhang, Zhe; Hao, Xuelong; Chen, Fei (Frontiers in Materials, 2021)
In this work, (3-aminopropyl)-triethoxysilane modified graphene oxide (GO) composite thin films have been synthesized on magnesium alloy AZ31 substrate. The structure, composition, and morphology of silane-GO films were analyzed. Electrochemical measurements and immersion tests have shown that silane-GO coatings provide effective protection for magnesium alloy substrate, owing to the good barrier property of layered GO and the defects decrease on GO film surface induced by the silane modification. In addition, the corrosion product between the outer silane-GO film and Mg-alloy substrate also improved the corrosion resistance of Mg-alloy. The silane-GO composite thin films provide an effective approach for protecting the lightweight metal substrate.